OBTENCIÓN DE PRE-FERMENTO NATURAL “MASA MADRE” PARA LA ELABORACIÓN DE PAN TIPO HOGAZA A PARTIR DE HARINA DE TRIGO E INTEGRAL - Feran Ibarra, Linder Isaac (2023)
This research study aims to promote the appreciation and adoption of natural Sourdough pre-ferments in a society that predominantly leans towards the traditional breadmaking that we are all familiar with. The focus of the research lies in comparing different time periods (1 week, 1 month, and 3 months) and types of flour (strong "000" flour and whole wheat flour, both from wheat) to identify the optimal conditions for obtaining pre-ferments, resulting in a total of six treatments. During this process, proximate analyses were carried out, including measurements of ash content, fiber, and pH, along with sensory evaluations conducted by a semi-trained panel consisting of 20 members.